Impacto de la automedicación en la duración de la hospitalización de niños con enfermedad diarreica aguda en un hospital de Loreto, 2024-2025 - Serrano Alayo, Yesbhel Saúl (2025)
Introduction: Self-medication is a global phenomenon that poses serious public health implications, especially in the context of diseases like acute diarrheal illnesses in children. In this regard, parents' decision to self-medicate their children without the supervision of a healthcare professional can result in severe consequences, including prolonged hospitalization of the children. This practice not only increases associated risks and costs but can also negatively impact the disease progression and the effectiveness of treatment. Objective: To determine the impact of self-medication on the duration of hospitalization of children with acute diarrheal illness in a hospital in Loreto, 2024-2025. Study Population: The study population will include 534 pediatric patients diagnosed with acute diarrheal illness admitted to the Pediatric Service of the Loreto Regional Hospital, 2024-2025. The sample will consist of 208 pediatric patients. Method: The research will be analytical, using an observational, prospective, case-control, and cross-sectional design. Results: To determine the proposed study results, the database will be imported from Excel into SPSS 26.0 software to perform statistical analysis. The descriptive analysis results will be presented with statistical values such as frequencies, percentages, mean, and standard deviation. For inferential analysis, the chi-square test and Fisher's exact test will be used to evaluate the association between dichotomous variables in small samples. A difference will be considered statistically significant if the p-value is less than 0.05, with a 95% confidence interval for hypothesis testing. Conclusions: The research aims to inform and strengthen public health strategies to ensure the appropriate use of medications and timely medical care to improve the management of these diseases.